BIMBINGAN KELOMPOK BERBASIS ONLINE DENGAN TEKNIK DISKUSI UNTUK SISWA SMP NEGERI 2 SOREANG YANG MEMILIKI MINAT BELAJAR BAHASA INGGRIS RENDAH - Ahmad Dimyati Mawaridz; Euis Eti Rohaeti; Tita Rosita (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2022)
This study aims to obtain results from the implementation of online-based group guidance with discussion techniques for students of SMP Negeri 2 Soreang who have low interest in learning English, student responses after being given online-based group guidance for students of SMP Negeri 2 Soreang who have low interest in learning English. , as well as the problems faced by BK teachers and students when implementing online-based group guidance services for studentsof SMP Negeri 2 Soreang who have low interest in learning English. This research is a descriptive study with a qualitative approach where observations, interviews and documentation are used for data collection. In this study, the research population was taken from class VIII-H of SMP Negeri 2 Soreang, totaling 38 students, by taking a sample of 6 students. Where before the service was given, students seemed not enthusiastic about participating in learning, less active and always late in collecting assignments. The online-based group guidance was carried out in four meetings. The discussion at the first meeting discussed broad interests, the second meeting discussed interest in learning, the third meeting discussed the problems faced by students and their solutions, and at the fourth meeting evaluation and follow-up were carried out. The results showed a good impact where students were eager to learn, active in learning and discussion and able to be on time in submitting assignments.Keywords: Group Guidance, group discussion technique, student interest in english learning